Assessing Challenges Face By Pakistan R&D Sector In Context Of Knowledge Management Capabilities - Zeeshan, Asim; Sorooshian, Shahryar (2017)
Developing new knowledge capabilities provides an opportunity to create new technologies that diverts conventional business approach to R&D and value creation models, by configuring knowledge and innovation as the significant strategic asset in creating balance sheet. Speedy variations in current technology trends and beginning of groundbreaking technologies are catalyzing huge boost in productivity and accelerating birth to new segment of economic activities. The purpose of this research study is to investigate present role of knowledge capability practices to facilitate R&D activities. This studies explores the information on existing challenges face by Pakistan R&D sector in context of implement knowledge management capabilities by assessing gaps of knowledge capabilities rank in global competitive index (GCI) develop by world economic forum (WEF) and global innovation index (GII) with respect to other regional and emerging economies.